2016
DOI: 10.4137/bmi.s38434
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine and Its Relation as a Biomarker in Nephrologic Diseases

Abstract: It is encouraging to observe that a search for publications on “asymmetric dimethylarginine (ADMA)” in PubMed, as updated on June 2016, yielded >2500 items, 24 years after a splendid paper published by Vallance et al in which the authors proposed that ADMA accumulation could be a cardiovascular risk factor in chronic kidney diseases. ADMA is the endogenous inhibitor of nitric oxide synthase and is related to endothelial dysfunction, which plays an important role in vascular damage elicited by various cardiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
0
10
1
2
Order By: Relevance
“…The more severe the kidney damage higher the value of Uacr and ADMA levels. [19][20][21] In patients with DM an increased of ADMA levels can occur but in this study, the majority of subjects in the DM group of non-DN (81.5%) had normal ADMA levels. Normal ADMA levels can be caused by the use of antioxidant drugs, estrogen, aspirin and vitamin A but the mechanism is unclear.…”
Section: Resultscontrasting
confidence: 53%
“…The more severe the kidney damage higher the value of Uacr and ADMA levels. [19][20][21] In patients with DM an increased of ADMA levels can occur but in this study, the majority of subjects in the DM group of non-DN (81.5%) had normal ADMA levels. Normal ADMA levels can be caused by the use of antioxidant drugs, estrogen, aspirin and vitamin A but the mechanism is unclear.…”
Section: Resultscontrasting
confidence: 53%
“…ADMA, a naturally occurring molecule, which is found in all human cells and plasma, can diffuse between cells (easy entry-exit), hence, it can be found in tissues and cells, besides being in circulation [25] . ADMA is an endogenous eNOS inhibitor whose accumulation leads to eNOS uncoupling, subsequent reduction in NO production and endothelial dysfunction [26] . Additionally, ADMA is not only a biomarker, but also a mediator of OS.…”
Section: Discussionmentioning
confidence: 99%
“…The literature comprises numerous studies investigating the relation of ADMA, which is a NO inhibitor, with ED and atherosclerosis. Experimental studies have demonstrated the relationship between the chronic ADMA increase and development of atherosclerosis and nephropathy . In addition, elevated ADMA concentrations were found to be associated with cardiovascular diseases and all‐cause mortality in ESRD and non‐diabetic CKD patients .…”
Section: Discussionmentioning
confidence: 99%